2005
DOI: 10.1063/1.1839554
|View full text |Cite
|
Sign up to set email alerts
|

Reflection absorption infrared spectroscopy and temperature programmed desorption investigations of the interaction of methanol with a graphite surface

Abstract: Reflection absorption infrared spectroscopy and temperature programmed desorption investigations of the interaction of methanol with a graphite surface Copyright and reuse:Sussex Research Online is a digital repository of the research output of the University.Copyright and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable, the material made available in SRO has been checked for eligibility befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
130
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(148 citation statements)
references
References 50 publications
16
130
2
Order By: Relevance
“…Hydrogen-bonded systems have previously been shown to exhibit fractional order desorption kinetics. 39,41,42 Evidence for a hydrogen bonded network within the water adlayer has also been shown in the broadness of the observed O-H stretching bands presented in the RAIR spectra (Figure 2).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Hydrogen-bonded systems have previously been shown to exhibit fractional order desorption kinetics. 39,41,42 Evidence for a hydrogen bonded network within the water adlayer has also been shown in the broadness of the observed O-H stretching bands presented in the RAIR spectra (Figure 2).…”
Section: Resultsmentioning
confidence: 88%
“…The gradient of such a plot is n, the order of desorption. 39 Note that, to perform this plot, it is assumed that the desorption energy and preexponential factor do not vary with coverage or temperature. The validity of these assumptions will be demonstrated later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparatus used for the experiments reported here has been described elsewhere, 59 hence only a brief description will be given. Experiments were performed in an ultra high vacuum (UHV) apparatus with a base pressure of r2 Â 10 À10 mbar.…”
Section: Methodsmentioning
confidence: 99%
“…New peaks were found only on certain sampling areas in the I region, and relatively thicker AFGP samples deposited from high concentrations gave fewer new peaks. Although the interaction mechanism of AFGP with HOPG needs to be clarified, the adsorption of molecules such as long n- 1 It has been reported that the long nalkane skeletal planes of monolayers of n-alkane molecules are oriented either perpendicular or parallel to the graphite (0001) surfaces; 14 CH 3 OH is physisorbed at all exposures and crystalline CH 3 OH can be formed on HOPG surface; 15 initial adsorption of AFP on a specific facet of ice can be randomly situated at first, but with high concentration of AFP, and the molecules align on the binding sites. 16 Therefore, it is reasonable to suggest that in samples deposited from low AFGP concentration, peptide backbone moiety of AFGP is parallel to the HOPG plane, while at high concentrations, the moiety is approximately perpendicular to the plane.…”
Section: Resultsmentioning
confidence: 99%